EVALUASI PROGRAM PELATIHAN KOMPUTER DI BALAI LATIHAN KERJA (BLK) KOMUNITAS PONPES AL-AITAM KABUPATEN BANDUNG - Ayi Najmul Hidayat; Sutisna - (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
The existence of BLK can be a place for the community to learn, increase knowledge, skills, exchange information and increase self-confidence. BLK as a center for education and potential development for the community has the task of organizing skills education in order to create employment opportunities in accordance with the real needs of the community. Computer training is also expected to be able to make the community, in this case the people of Bandung Regency, have knowledge of computer technology. To find out the context, input, process, and product as well as assess the success of a program objective faced in this case computer training, it is necessary to hold an evaluation of the training program. This study aims to evaluate the computer training program at the Al-Aitam Islamic Boarding School Community BLK Bandung Regency using the CIPP evaluation model (Context, Input, Process, Product). This study uses a qualitative description approach. Data collection is done by observation, interviews and documentation. Proof of data validity using triangulation techniques. The research results obtained in this study are that there is an increase in the quality of students in computer training programs and the percentage of students passing is 100%. It is in accordance with the indicators of achievement of computer training programs. The results of the evaluation of the computer training program are that the program can be continued with several improvements and improvements in order to produce maximum training program services and produce quality and quantity of graduates who are truly competent and professional in the field of computers.